Studi Perbandingan Kesiapan Masyarakat Menghadapi New Normal Covid-19 Di Kota Salatiga Dan Kota Jayapura - Patrick Leonardo Alexander Hamadi; Fiane de Fretes; Sanfia Tesabela Messakh (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Coronavirus Disease 2019 or known as COVID-19 has currently disturbed 119 countries in the world, one of which is Indonesia. This condition then requires the government to make various efforts to overcome it, one of which is the New Normal. New Normal is a change in the behavior of people who carry out normal activities, but must be accompanied by health protocols. The purpose of this study was to compare the readiness of the people of productive age in Salatiga City and Jayapura City to face the New Normal. The method used in this study is comparative analysis, with analysis of the Independent T-score test or T-test using the SPSS application. The population of this research is people in Salatiga City and Jayapura City. The research sample uses representative characteristics of each population. The sampling technique is random sampling. The results of this study indicate that the community's readiness to face the New Normal in Salatiga City is 72.02 and in Jayapura City is 77.96. Based on these results, it can be concluded that the people in Salatiga City and in Jayapura City have a significant difference in readiness and the level of readiness of the people in Jayapura City in facing the New Normal is better.